DIFFERENCES IN PREVALENCE OF EARLY CHILDHOOD CARIES (ECC) IN STUNTING AND NON-STUNTING CHILDREN IN BANDUNG - Mulsin, Jenny Imanuel (Odonto : Dental Journal, 2024)
Background: ECC (early childhood caries) has become a significant oral health problem in children. ECC in children can cause pain that could interferes nutritional intake. Meanwhile, malnutrition conditions can roughen the enamel surface, affect the salivary glands, reduced salivary flow rate, affect the salivary composition and pH to a lower level thereby increased the risk of ECC. This study aims to determine differences in prevalence of ECC on stunted and non-stunted children. Method: This research was conducted using an observational analytic method with a cross-sectional study design. The ICC value (intraclass correlation coefficient) was obtained at 0.93. The collection of ECC prevalence data was carried out in April-May 2023 in Antapani Tengah and Antapani Kidul, Bandung. Data collection was carried out by examining the teeth and oral cavity in stunted and non-stunted children. The results of the research data were tested by using the Chi-Square test. Result: The average value of the def-t index for stunted children was 6.43 and 5.23 for non-stunted children. Both sample groups are included in the high category according to WHO (World Health Organization). The prevalence of ECC in stunted children was found to be 93.3% while the prevalence of ECC in non-stunted children was 73.3%. Chi-square test results show a p-value of 0.006 which indicates a p-value